2021
DOI: 10.1037/cpp0000416
|View full text |Cite
|
Sign up to set email alerts
|

The impact of family bereavement interventions: Qualitative feedback identifies needs.

Abstract: Objective: To present a synthesis of program improvement evaluations of two approaches to bereavement support for families: (a) weekend family camps providing developmentally targeted grief education and social support for children and parents, and (b) a wait-list control randomized trial of a parent bereavement group intervention. Method: Families eligible for camp experienced a child's death (from any cause) and have surviving children at home. No-cost twice-yearly weekend camps include support sessions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 25 publications
(35 reference statements)
1
19
0
Order By: Relevance
“…It is the first study in pediatric chronic pain to include an in-depth thematic analysis of parent perspectives in participating in a parenttargeted, group-based intervention (that was delivered either in-person or virtually). In general, parents have reported generally good feasibility and acceptability of parent interventions for pediatric chronic pain; 6 however, results from this analysis, specifically those regarding the social benefits of a group for parents, are consistent with analyses of feedback from parents in other interventions including bereavement groups, 25 as well as parent interventions related to Autism and eating disorders. 14,26 Thus, this study contributed to a more detailed and nuanced understanding of the most important treatment components to consider for pediatric chronic pain from parents' own perspectives.…”
Section: Discussionsupporting
confidence: 66%
“…It is the first study in pediatric chronic pain to include an in-depth thematic analysis of parent perspectives in participating in a parenttargeted, group-based intervention (that was delivered either in-person or virtually). In general, parents have reported generally good feasibility and acceptability of parent interventions for pediatric chronic pain; 6 however, results from this analysis, specifically those regarding the social benefits of a group for parents, are consistent with analyses of feedback from parents in other interventions including bereavement groups, 25 as well as parent interventions related to Autism and eating disorders. 14,26 Thus, this study contributed to a more detailed and nuanced understanding of the most important treatment components to consider for pediatric chronic pain from parents' own perspectives.…”
Section: Discussionsupporting
confidence: 66%
“…The first one consists in a bereavement programme at St. Jude Children’s Research Hospital where parents and families had the opportunity to participate in clinical interventions conducted by a bereavement coordinator (Snaman et al, 2016 ). Secondly, the study carried out by Henning et al ( 2021 ) consisted in the implementation of two different interventions and their subsequent comparison. The first one consisted in free weekend family camps organized twice a year where families received grief psychoeducation.…”
Section: Resultsmentioning
confidence: 99%
“…More concretely, 81% of parents when asked about the usefulness of one of the components of the programme, indicated that it was helpful and beneficial for them. Next, another positive impact of a family bereavement intervention was observed in the results obtained by Henning et al (2021). The authors state that both groups of participants identified benefits such as: improved mood and coping capacities, enhanced relationships and communication within their families, as well as a better overall mental health due to their involvement in the intervention.…”
Section: Interventions With Healing Effects On Parental Bereavementmentioning
confidence: 90%
“…Findings underscore the potential role of pediatric psychologists as family advocates, aiming to minimize the familial and societal implications of physical, cognitive, and psychological morbidities parents experience in the face of loss. Finally, Henning et al (2021) synthesize qualitative findings from two avenues of support for bereaved parents: a weekend family camp focused on grief education and social support, and a postintervention focus group from a wait-list controlled randomized trial of a group-based intervention for bereaved parents. Authors share insights on families' expressed needs related to bereavement care and follow-up.…”
Section: Where We Have Been: Psychologists In Palliative Carementioning
confidence: 99%
“…Authors emphasize clinical implications and offer concrete recommendations for PPC clinicians, which we anticipate will be of the highest value to readers. These include conversational prompts and concrete strategies for intervening in cases where caregivers request nondisclosure (Brown et al, 2021), parent-driven recommendations for programming and direct support for bereaved parents (Clark et al, 2021; Dias et al, 2021; Henning et al, 2021), clinical intervention targets for parents during active treatment (Fisher et al, 2021), and guidance for providing culturally sensitive clinical services (Kentor et al, 2021; Lyon et al, 2021; Sample et al, 2021).…”
Section: Where We Are: An Introduction To the Special Issuementioning
confidence: 99%